Microbiome matters: how transplantation methods and donor origins shape the successful restoration of the seagrass Posidonia oceanica - Arnaud Boulenger; Tânia Aires; Aschwin H. Engelen; Gerard Muyzer; Michel Marengo; Sylvie Gobert (Environmental Microbiome)
Abstract Background Posidonia oceanica forms extensive seagrass meadows in the Mediterranean Sea, providing key ecosystem services. However, these meadows decline due to anthropogenic pressures like anchoring and coastal development. Transplantation-based restoration has been explored for decades, yet the role of the plant-associated microbiome in restoration success remains largely unknown. Results 16 S rRNA gene amplicon sequencing was used to investigate how different transplantation methods and donor origins influence the bacterial communities of P. oceanica cuttings two years post-transplantation. We tested three transplantation methods, iron staples, coconut fiber mats, and BESE elements, and compared them with control meadows and donor populations from two different origins: naturally uprooted storm-fragments and intermatte cuttings manually harvested from established meadows. Our results show that transplantation methods strongly shape bacterial communities in seagrass roots. Iron staples promoted microbial assemblages most similar to natural meadows, likely due to direct sediment contact enhancing recruitment of key functional bacterial orders such as Chromatiales and Desulfobacterales. In contrast, BESE elements and coconut fiber mats displayed dissimilar bacterial communities compared to control meadows, likely due to material composition and physical separation between the cuttings and the sediment. Donor origin had only subtle effects on bacterial communities’ structure, although intermatte cuttings showed higher abundances of Candidatus Thiodiazotropha, a genus thought to be involved sulfur oxidation and nitrogen fixation. Conclusion Our results demonstrate that transplantation methods strongly influence root-associated bacterial communities. Limited sediment contact in elevated substrates delayed the establishment of key functional bacteria, highlighting the importance of direct interaction with the sediment microbial pool. These results imply that restoration strategies should prioritize methods enhancing sediment–root interactions to support microbial recovery. Incorporating microbiome considerations, such as optimized substrates or microbial inoculation, could improve the resilience and long-term success of P. oceanica restoration.